A systematic review of patient-reported measures of burden of treatment in three chronic diseases - Eton DT; Elraiyah TA; Yost KJ; Ridgeway JL; Johnson A; Egginton JS; Mullan RJ; Murad MH; Erwin PJ; Montori VM (Patient Related Outcome Measures, 2013)
David T Eton,1 Tarig A Elraiyah,2 Kathleen J Yost,3 Jennifer L Ridgeway,1 Anna Johnson,2 Jason S Egginton,1 Rebecca J Mullan,4 Mohammad Hassan Murad,2 Patricia J Erwin,2 Victor M Montori1,2 1Division of Heath Care Policy and Research, Department of Health Sciences Research, 2Knowledge and Evaluation Research Unit, 3Division of Epidemiology, Department of Health Sciences Research, Mayo Clinic, Rochester, MN, USA; 4University of Minnesota Medical School, Minneapolis, MN, USA Background: Burden of treatment refers to the workload of health care and its impact on patient functioning and well-being. There are a number of patient-reported measures that assess burden of treatment in single diseases or in specific treatment contexts. A review of such measures could help identify content for a general measure of treatment burden that could be used with patients dealing with multiple chronic conditions. We reviewed the content and psychometric properties of patient-reported measures that assess aspects of treatment burden in three chronic diseases, ie, diabetes, chronic kidney disease, and heart failure. Methods: We searched Ovid MEDLINE, Ovid EMBASE, Ovid PsycINFO, and EBSCO CINAHL through November 2011. Abstracts were independently reviewed by two people, with disagreements adjudicated by a third person. Retrieved articles were reviewed to confirm relevance, with patient-reported measures scrutinized to determine consistency with the definition of burden of treatment. Descriptive information and psychometric properties were extracted. Results: A total of 5686 abstracts were identified from the database searches. After abstract review, 359 full-text articles were retrieved, of which 76 met our inclusion criteria. An additional 22 articles were identified from the references of included articles. From the 98 studies, 57 patient-reported measures of treatment burden (full measures or components within measures) were identified. Most were multi-item scales (89%) and assessed treatment burden in diabetes (82%). Only 15 measures were developed using direct patient input and had demonstrable evidence of reliability, scale structure, and multiple forms of validity; six of these demonstrated evidence of sensitivity to change. We identified 12 content domains common across measures and disease types. Conclusion: Available measures of treatment burden in single diseases can inform derivation of a patient-centered measure of the construct in patients with multiple chronic conditions. Patients should take part in developing the measure to ensure salience and relevance. Keywords: patient-reported outcomes, treatment burden, questionnaire, psychometric properties, self-management, patient-centered